THE INFLUENCE OF BASEL III ON ISLAMIC BANK RISK - Ding, Xiaoling; Haron, Razali; Hasan, Aznan (Journal of Islamic Monetary Economics and Finance, 2023)
This paper investigates the impact of bank regulatory capital on Islamic bank risk using bank-level data from 29 countries covering the period from 2004 to 2020. Applying the generalized method of moments technique on dynamic panels, we discover that on average Islamic bank regulatory capital ratios exceed the level required by Basel III. The findings provide evidence in support of the moral hazard hypothesis; that is, there is a negative relationship between capital and risk. They indicate that Islamic banks are better protected against risk when they fulfill Basel III and IFSB regulatory capital requirements. According to our findings, authorities that aim to improve the financial stability of the banking industry should reinforce their policies and oblige banks to adhere to regulatory capital requirements during crises such as Covid-19. Finally, we observe that different risk indicators have diverse correlations with regulatory capital, and that the findings are robust across a variety of estimation methodologies.